2009
DOI: 10.1007/s00534-009-0206-3
|View full text |Cite
|
Sign up to set email alerts
|

Major hepatectomy for perihilar cholangiocarcinoma

Abstract: Background/purpose Hilar cholangiocarcinoma and intrahepatic cholangiocarcinoma involving the hepatic hilus are defined as ''perihilar cholangiocarcinoma''. The principle of surgical treatment is hemi-hepatectomy or trisectionectomy of the liver, caudate lobectomy, and resection of the extrahepatic bile duct for complete resection of the tumor. The aim of this study was to review the outcomes of major hepatectomy for perihilar cholangiocarcinoma. Methods Using the Kaplan-Meier method and the Cox proportional h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 35 publications
3
53
0
2
Order By: Relevance
“…Our finding is in line with that of Kosuge et al (1999), who found that patients with a positive resection margin (R1) had a 2.88 times higher mortality risk. The finding was also similar to those reported in other studies (Jarnagin et al, 2005;Witzigmann et al, 2006;Yubin et al, 2008;Unno et al, 2010;Murakami et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our finding is in line with that of Kosuge et al (1999), who found that patients with a positive resection margin (R1) had a 2.88 times higher mortality risk. The finding was also similar to those reported in other studies (Jarnagin et al, 2005;Witzigmann et al, 2006;Yubin et al, 2008;Unno et al, 2010;Murakami et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…Studies about survival rates or factors affecting the survival of CCA patients after resection, especially those with extrahepatic CCA, are rare, and the results vary from one country to another (Bhudhisawasdi, 1997;Khuntikeo, 2008;American Cancer Society, 2009;Unno et al, 2010). The aim of this study was therefore to evaluate the survival rates and factors affecting survival in extrahepatic CCA patients following surgical treatment at Srinagarind Hospital, Khon Kaen University, Thailand.…”
Section: Survival Rate Of Extrahepatic Cholangiocarcinomamentioning
confidence: 99%
“…In fact, combined caudate lobe resection is considered as a standard surgical procedure for these diseases in Japan. Japanese high volume centers in which combined caudate lobe resection is routinely performed report relatively high curative resection rate (59-87%) and 5 year survival rate (33-44%) [74,87,124,127,[142][143][144][145][146][147][148]. Several reports from other countries also showed the benefits of this procedure for hilar/upper bile duct carcinoma [149][150][151][152][153][154].…”
Section: Cq16: What Are Considered As Unresectable Factors In Biliarymentioning
confidence: 99%
“…Reports from high-volume centers during the last decade are summarized in Table 2 [26, 45,71,73,128,135,142,[146][147][148][149][150][151][152][153][154][155][156][157][158][159][160] . The overall 3-and 5-year survival rates after radical surgery ranged from 37% to 60% and 20% to 42%, respectively.…”
Section: Extended Hepatectomy For Hilar Cholangiocarcinomamentioning
confidence: 99%